Perona‐Malik equation ‐ error estimates for explicit finite volume scheme - Handlovičová, A.; Krivá, Z. (Mathematical Modelling and Analysis, 2005)
Error estimates in the L2 norm for the explicit fully discrete numerical finite volume scheme are derived and proved for Perona‐Malik equation. Numerical example is also presented. First Published Online: 14 Oct 2010